Developing an Interactive Arabic Learning Module through Bima Language Loanwords - Zuhriyah, Nurul; Wahyuningsih, Sri; Ningrum, Nadiah Hutami; Mariati, Mariati; Sudarsono, Sudarsono (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
The widespread use of Arabic loanwords in the Bima language has not been systematically integrated into Arabic instruction, creating a gap in contextual learning materials. This study develops an interactive module based on Arabic–Bima loanwords, grounded in the Contextual Teaching and Learning (CTL) approach and supported by Culturally Responsive Teaching (CRT). Using the Borg and Gall R&D model, five stages were completed: needs analysis, product design, expert validation, field testing, and revision, using a mixed-methods approach combining quantitative tests and qualitative feedback. Expert evaluations rated the module highly feasible (90–95%). Field trials at MAN 2 Kota Bima and MAN 2 Bima showed statistically significant improvement based on the Wilcoxon test (p = 0.000) and greater gains based on the Mann-Whitney test (p < 0.05). Teacher ratings (94–98%) and student feedback confirmed strong acceptance. The findings confirm the innovative potential of Arabic–Bima loanwords as an effective contextual and culturally responsive resource in Arabic language learning.